The Effect of Intellectual Capital Disclosure Disclosure on Profitability and Firm Value in Banking Companies Listed on the Stock Exchange 2015-2019: Pengaruh Pengungkapan Intellectual Capital Disclosure Terhadap Profitabilitas Dan Nilai Perusahaan Pada Perusahaan Perbankan Yang Terdaftar Di Bei Tahun 2015-2019 - Esty Nugraheni; Nurasik (Academia Open, 2021)
This study aims to analyze the effect of intellectual capital disclosure on financial performance and firm value in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 14 banking companies listed on the IDX in the 2015-2019 period. The data used is secondary data. The data analysis method used in this research is PLS 3.2. The results of this study indicate that Intellectual Capital Disclosure affects the company's financial performance (ROA) in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Intellectual Capital Disclosure has an effect on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period.